2004
DOI: 10.1046/j.1399-0012.2003.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Delay of CMV infection in high‐risk CMV mismatch lung transplant recipients due to prophylaxis with oral ganciclovir

Abstract: Cytomegalovirus (CMV) is a common opportunistic infection in lung transplant recipients. Despite the use of early post-operative intravenous ganciclovir, most high-risk patients develop CMV infection. We conducted this retrospective study to determine the efficacy of extended CMV prophylaxis with oral ganciclovir in high-risk, donor-positive-recipient-negative, lung recipients. All patients initially received 3 months of intravenous ganciclovir and CMV hyperimmune globulin. Clinical outcomes in all CMV mismatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
4
24
1
2
Order By: Relevance
“…Moreover, with this type of prophylaxis, there is a nearly 10% rate of ganciclovir-resistant infection (8,10). The reported incidence of CMV disease with oral ganciclovir is around 30% (7,15), whereas in the present study it was 16.1%. …”
Section: The Second Most Frequent Cause Of Infectious Complications Fcontrasting
confidence: 54%
“…Moreover, with this type of prophylaxis, there is a nearly 10% rate of ganciclovir-resistant infection (8,10). The reported incidence of CMV disease with oral ganciclovir is around 30% (7,15), whereas in the present study it was 16.1%. …”
Section: The Second Most Frequent Cause Of Infectious Complications Fcontrasting
confidence: 54%
“…Small retrospective studies indicated that routine use of ganciclovir for CMV prophylaxis perioperatively decreased CMV disease and delayed the onset of BOS as compared with no prophylaxis (5,6). Consequently, most lung transplantation centers routinely employ a fixed duration of intravenous ganciclovir and/or oral valganciclovir prophylaxis immediately after transplantation.…”
mentioning
confidence: 99%
“…To support the relevance of the outcome in our small control population, we performed an exhaustive search of the Medline database and compiled all available articles that contained a full data set for patients who underwent lung transplantation ( ) during 1982-1999 n p 274 and who had not received CMV prophylaxis. Data with respect to the incidence of CMV-related events and disease from 4 observational studies [1][2][3][4] and from the historical control subjects of 5 nonrandomized trials of ganciclovir prophylaxis [5][6][7][8][9] were compared with data from the current series. With respect to BOS and survival, data were available for only 139 cases reported in the literature [4,5,8,9].…”
mentioning
confidence: 99%